Reference evapotranspiration estimation by the Irrigameter in Southern Tocantins State, Brazil - Luan B. Giovanelli; Rubens A. Oliveira; Jair C. Oliveira-Filho; Júlio C. M. Baptestini; Fábio T. Delazari; Gilberto C. Sediyama (Revista Brasileira de Engenharia Agrícola e Ambiental)
ABSTRACT The choice for the most appropriate method to estimate evapotranspiration depends on the availability of meteorological data, required level of precision and cost of equipment acquisition. For this estimate, the Irrigameter is simple to operate, precise and economically viable to farmers. In addition, it collaborates in the application of the necessary water depth to crops, thus avoiding unnecessary energy consumption, environmental degradation, and increasing crop yield and improving crop quality. In this context, the objective of this research was to estimate the reference evapotranspiration using the Irrigameter, for the climatic conditions of the Southern Tocantins state, Brazil. The experimental design was completely randomized with Irrigameters operating with seven water heights in the evaporator, as treatments, with three replicates. The reference evapotranspiration was obtained by FAO-56 Penman-Monteith method. For the analyzed climatic conditions, the water height in the evaporator recommended to estimate the reference evaporation in the spring is 3.4 cm; summer, 4.0 cm; fall, 3.8 cm; and winter, 2.3 cm.